Identification of first active compounds in drug discovery. how to proceed? - Giraud, Stéphane (Frontiers in Drug Discovery, 2024)
In the quest for the discovery of new therapies, the identification of the initial active molecules is a major challenge. Although significant progress in chemistry and biology has been made in recent years, the process remains difficult. In this mini-review, we will explain the major approaches and experimental methods that can be used to identify these molecules. Two main approaches are described, target-based and phenotypic-based and a focus is made on some high throughput technologies and biophysical methods.